Tir-induced actin remodeling triggers expression of CXCL1 in enterocytes and neutrophil recruitment during Citrobacter rodentium infection - Frankel,GM; Habibzay,M; Crepin-Sevenou,V; Glegola-Madejska,I; Guenot,M; Collins,J (Infection and Immunity, 2015)
The hallmarks of enteropathogenic Escherichia coli (EPEC) infection are formation of attaching and effacing (A/E) lesions on mucosal surfaces and actin-rich pedestals on cultured cells, both dependent on the type III secretion system effector Tir. Following translocation into cultured cells and clustering by intimin, Tir Y474 is phosphorylated leading to recruitment of Nck, activation of N-WASP and actin polymerization via the Arp2/3 complex. A secondary, weak, actin polymerization pathway is triggered via an NPY motif (Y454). Importantly, Y454 and Y474 play no role in A/E lesion formation on mucosal surfaces following infection with the EPEC-like mouse pathogen Citrobacter rodentium. In this study we investigated the roles of Tir segments located upstream of Y451 and downstream of Y471 in C. rodentium colonization and A/E lesion formation. We also tested the role Tir residues Y451 and Y471 play in host immune responses to C. rodentium infection. We found that deletion of amino acids 382-462 or 478-547 had no impact on the ability of Tir to mediate A/E lesion formation, although deletion of amino acids 478-547 affected Tir translocation. Examination of enterocytes isolated from infected mice revealed that a C. rodentium expressing Tir_Y451A/Y471A recruited significantly less neutrophils to the colon and triggered less colonic hyperplasia on day 14 post infection, compared to infection with the wild type strain. Consistently, enterocytes isolated from mice infected with C. rodentium expressing Tir_Y451A/Y471A expressed significantly less CXCL1. These result show that Tir-induced actin remodeling plays a direct role in modulation of immune responses to C. rodentium infection.